Poplar and shrub willow energy crops in the United States: field trial results from the multiyear regional feedstock partnership and yield potential maps based on the PRISM‐ELM model. Issue 10 (20th February 2018) - Volk, Timothy A.; Berguson, Bill; Daly, Christopher; Halbleib, Michael D.; Miller, Raymond; Rials, Timothy G.; Abrahamson, Lawrence P.; Buchman, Dan; Buford, Marylin; Cunningham, Michael W.; Eisenbies, Mark; Fabio, Eric S.; et al.
Abstract: To increase the understanding of poplar and willow perennial woody crops and facilitate their deployment for the production of biofuels, bioproducts, and bioenergy, there is a need for broadscale yield maps. For national analysis of woody and herbaceous crops production potential, biomass feedstock yield maps should be developed using a common framework. This study developed willow and poplar potential yield maps by combining data from a network of willow and poplar field trials and the modeling power of PRISM‐ELM. Yields of the top three willow cultivars across 17 sites ranged from 3.60 to 14.6 Mg ha −1  yr −1 dry weight, while the yields from 17 poplar trials ranged from 7.5 to 15.2 Mg ha −1  yr −1 . Relationships between the environmental suitability estimates from the PRISM‐ELM model and results from field trials had an R 2 of 0.60 for poplar and 0.81 for willow. The resulting potential yield maps reflected the range of poplar and willow yields that have been reported in the literature. Poplar covered a larger geographic range than willow, which likely reflects the poplar breeding efforts that have occurred for many more decades using genotypes from a broader range of environments than willow. While the field trial data sets used to develop these models represent the most complete information at the time, there is a need to expand and improve the model by monitoring trials over multiple cutting cycles and across a broader range of environmental gradients. Despite some limitations, the results of these models represent a dramatic improvement in projections of potential yield of poplar and willow crops across the United States. Abstract : To increase the understanding of poplar and willow perennial woody crops and facilitate their deployment for the production of biofuels, bioproducts, and bioenergy there is a need for broad scale yield maps. This study developed willow and poplar potential yield maps by combining data from a network of field trials and the modeling power of PRISM‐ELM. This map shows the potential willow biomass yields for the US generated from the PRISM‐ELM model and data from a network of field trials.